Analisis Isi Strategi Personal Branding Ziko Harnadi Sebagai Content Creator Otomotif dan Drifter Pada Akun Instagram @zikoi - Hilmi Akbar; Diana Amalia (Hulondalo Jurnal Ilmu Pemerintahan dan Ilmu Komunikasi, 2026)
This study aims to analyze how personal branding strategies are represented in the visual content of the Instagram account @zikoi, owned by Ziko Harnadi, a public figure in the automotive and drifting scene. A descriptive qualitative approach was employed, using content analysis on 30 selected posts consisting of photos and videos uploaded over a defined period. The analysis focused on visual elements such as color tone, composition, visual expressions, and the accompanying narrative context. The results show that Ziko’s personal branding is constructed through consistent visual aesthetics characterized by dominant masculine tones, a professional image through drifting activities, and cinematic elements that enhance the impression of dynamism and competence. Additionally, Ziko presents a personal side that fosters emotional closeness with the audience, strengthening the perception of authenticity and credibility. This strategy highlights the importance of visual and narrative consistency in shaping a strong digital identity. Practically, the study offers insights into how individuals can strategically utilize social media to build a professional image. Academically, the findings contribute to the development of visual communication and personal branding studies in the digital era, particularly on visually driven platforms such as Instagram.